FOSTERING COLLEGE STUDENT'S CRITICAL READING SKILL THROUGH PADLET APPLICATION - Vina Nurviyani (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2018)
AbstractCritical reading is an essential skill for college students success in academic and social engagement. Many students have troubles in reading the required books or references in some courses. Thus, this study aimed to investigate the effectiveness of padlet application as an instructional media in fostering college students critical reading skill in higher education. Moreover, the strengths and the weaknesses of the padlet application in teaching critical reading were explored. This study applied action research was conducted in two cycles and involved twenty five college students. It was carried out at a private university in West Java. Moreover, three data collection techniques were applied in this study including reading tests, classroom observations, and questionnaire. The finding shows that by implementing padlet application in fostering college students critical reading skill covering questioning, discussing, interpreting, summarizing and synthesizing, in the first cycle, most college students critical reading skill achieved much improvement obviously. Sixty percents of all students reached the learning outcomes in critical reaading. Furthermore, in the second one, after carrying out a deep analysis and remedial teaching, eighty percents of them reached the learning outcome in critical reaading. It means that almost all college students critical reading skill increased significantly. Thus, the implementation of padlet application in fostering students critical reading skill is effective with the result showing significant difference, compared with that of the first cycle.Keywords: action research, critical reading, padlet application.